Law, judiciary, and justice in India - Sehgal, Brinder Pal Singh, 1951- (New Delhi : Deep & Deep Publications, 1993)
Papers and proceedings of a seminar held on March 16, 1991.
Includes and index.
Keywords: Justice, Administration of -- India; Political questions and judicial power -- India; Law -- Political aspects